A Feasiblity Study on the Establishment of Eye Painters in Phase 4 Bagong Silang Caloocan City (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
As the finds, paintings of miniature buffalos, warty pigs and human hands covering the walls and ceilings of caves in Indonesia are considered as the oldest examples of cave art in the world. Filipinos began creating paintings in the European tradition during the 17th-century Spanish period. The earliest of these paintings were Church frescoes, religious imagery from Biblical sources, as well as engravings, sculptures and lithographs featuring Christian icons and European nobility. Due to modern technologies youths are no longer enjoying the painting because nowadays, just one click on the internet they can quickly see variety of paintings and copy paste it. But still, it's different when you've done it by yourself and work hard for it. The study adopted a descriptive and quantitative type of research. The business utilized 100 respondents from the identified research locale to know their perception about the service. The researchers conducted survey, unemployed-10, employed-30, students-37, self-employed-23 and a total of 100 respondents in the area. The most of the prospective customers of the Eye Painters lives around Phase 4 Bagong Silang Caloocan City are the people who love painting. The proponents create a survey questionnaire for 100 respondents. The fulfillment of the needs and wants ofits customers or target market must be the key objective of the recommended business. According to the researchers’ survey, majority of the respondents around the location of the business who love to paint are unemployed 10%, employed 30%, self-employed 23% and students 37%. According to the survey, 90% loves to paint and 10% is not sure which is very important to know the success prediction of the business.EYE PAINTERS will offer affordable painting equipment, the business will focus on selling various painting equipment and selling different sizes of frames. The target markets are students and artists. It ideally suits both artists and students who enjoy drawing and painting outdoors in the studio. Most people who choose to paint are passionate and know how to appreciate the art. The purpose is to share the same passion to the customers where they can enjoy the output of paintings, either by themselves or by using various painting equipment.
Keywords: paintings, hobby